Analysis of the positions of the Constitutional Court of the Russian Federation on issues of protection of historical memory - Kirnosov, Ivan Denisovich (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. In recent decades, the issues of preserving and protecting historical memory have become increasingly relevant in the context of legal regulation and judicial practice. The purpose of this article is to study the positions of the Constitutional Court of the Russian Federation in the field of historical memory protection, as well as to determine their impact on national legal consciousness and legislation. Theoretical analysis. The article considers the positions of constitutional researchers on the role of the Constitutional Court in the field of direct application of the provisions of the Constitution, on the basis of which, in turn, the direction of development of the position of the Constitutional Court of the Russian Federation on the protection of historical memory is studied. Empirical analysis. The study includes a detailed analysis of the key decisions of the Constitutional Court of the Russian Federation related to the protection of historical memory. Specific cases through which the court formulated its approaches to historical and legal issues are analyzed. Results. Several key aspects characterizing the approach of the Constitutional Court of the Russian Federation to the issue of historical memory are highlighted. Firstly, the Constitutional Court is aware of its importance as an element that strengthens national identity and social unity. Special attention is paid to respect for the defenders of the Fatherland, whose role is enshrined in a number of decisions of the Constitutional Court. Continuity in the development of the state is also one of the key constitutionally significant values supported by the legal positions of the Constitutional Court. Secondly, the Constitutional Court emphasizes the importance of maintaining a balance of interests between preserving historical memory and exercising citizens’ rights and freedoms. Since the protection of historical memory, in particular the preservation of cultural monuments, may overlap with various legal and public spheres, the Constitutional Court is forced to integrate its protection into a complex system of rights and obligations of citizens and the state. Thirdly, the firm and unwavering positions of the Constitutional Court on countering the spread of fascist ideology, the public display of Nazi symbols or paraphernalia as insulting to the multinational people and the memory of the victims suffered in the Great Patriotic War, the inadmissibility of denying crimes against humanity established by the Nuremberg Tribunal, serve as the basis of legal policy to perpetuate the Victory of the Soviet people in the Great Patriotic War.